2016
DOI: 10.1155/2016/4567940
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Modified Pin Profile and Process Parameters on the Friction Stir Welding of Aluminum Alloy 6061-T6

Abstract: This work deals with the effect of a new “bolt-head” pin profile on the friction stir welding performance of the aluminum alloy 6061-T6, compared to traditional pin profiles. Friction stir welding parameters such as the tool rotation speed and the welding speed were investigated together with the different pin profiles; the results show that the new “bolt-head” pin profile leads to better mechanical properties of welded specimens. The pin profiles used in this work were the straight square (SS), straight hexag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…were focused on the tool geometry in FSW process. Juarez et al (Verduzco Ju arez et al, 2016) have studied the effect on FSW of aluminium alloys Al6061 with modified tool pin, confirmed that the straight hexagon bolthead kind of tool pin provides a good amount of flow of material during welding. However, Fujji et al (Fujii et al, 2006) found that while performing FSW with aluminium alloys the tool shape is not significant to achieve better mechanical properties at lower rotational speed (600 rpm).…”
Section: Introductionmentioning
confidence: 93%
“…were focused on the tool geometry in FSW process. Juarez et al (Verduzco Ju arez et al, 2016) have studied the effect on FSW of aluminium alloys Al6061 with modified tool pin, confirmed that the straight hexagon bolthead kind of tool pin provides a good amount of flow of material during welding. However, Fujji et al (Fujii et al, 2006) found that while performing FSW with aluminium alloys the tool shape is not significant to achieve better mechanical properties at lower rotational speed (600 rpm).…”
Section: Introductionmentioning
confidence: 93%
“…Careful thermal insulation is done with help of foam (polymer in nature) in order to prevent being affected by external heat during the transfer. e nozzle is availed to point the fluid towards the friction stir welding zone [12,[14][15][16][17][18][20][21][22]]. An AWM720P1 flow sensor is availed to ensure a constant volume flow rate for liquid nitrogen at 1 bar pressure atmospheric pressure which is 1.977 litres/minute, by taking the total head loss in consideration, elevation point of the FSW setup, and having initial velocity and exit pressure to be zero.…”
Section: Development Of Cryogenic-assisted Friction Stir Weldingmentioning
confidence: 99%
“…Another major factor of oil coolants is in the area of formation of fumes and gases which when exposed in the welding environment causes long-term health deteriorations [13]. So, given the scenario, dry FSW was concluded to be a cleaner operation along with being cost effective in nature [5,14].…”
Section: Introductionmentioning
confidence: 99%
“…journal.ump.edu.my/ijame ◄ investigation were kept constant at rotation speed of 1000 rpm, feed speed of 90 mm/min, penetration speed of 9 mm/min, and holding time of 10 seconds. The last parameters were selected to reduce the defects of welding [21].…”
Section: Experimental Details Materials and Welding Parametersmentioning
confidence: 99%